2011
DOI: 10.1590/s0100-54052011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Incubation period of Hemileia vastatrix in coffee plants in Brazil simulated under climate change

Abstract: Risk analysis of climate change on plant diseases has great i m p o rt a n c e f or a gr i c u l t u re s i n c e i t a l lo ws t h e e va lu a t i o n of management strategies to minimize future damages. This work a i m e d t o s i m u la t e f u t u re s c e n a ri o s of c off ee r u s t ( H e m i l e i a vastatrix) epidemics by elaborating geographic distribution maps using a model that estimates the pathogen incubation period and the output from three General Circulation Models (CSIRO-Mk3. 2050s and 2080s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 8 publications
1
25
0
9
Order By: Relevance
“…This was attributed to increased minimum temperatures during the winter. Ghini et al (2011) showed a trend towards a reduction in the duration of the latency period of the disease in the future, and, hence, to an increase in epidemic intensity, due to increased temperatures. Coffee rust is not the only pest to fear.…”
Section: Coffee Rust In the Futurementioning
confidence: 99%
“…This was attributed to increased minimum temperatures during the winter. Ghini et al (2011) showed a trend towards a reduction in the duration of the latency period of the disease in the future, and, hence, to an increase in epidemic intensity, due to increased temperatures. Coffee rust is not the only pest to fear.…”
Section: Coffee Rust In the Futurementioning
confidence: 99%
“…Plant health is predicted to generally suffer under climate change through a variety of mechanisms, from accelerated pathogen evolution and shorter incubation periods to enhanced abiotic stress due to mismatches between ecosystems and their climate and the more frequent occurrence of extreme weather events (Chakraborty and Datta 2003;Chakraborty 2005;Ghini et al 2011b;Sutherst et al 2011). Drought is expected to lead to increased frequency of tree pathogens, mainly through indirect effects on host physiology (Desprez- Loustau et al 2006).…”
Section: Direct Effects Of Climate Change On Plant Pathosystemsmentioning
confidence: 99%
“…Simulações com temperaturas máximas e mínimas para os cenários futuros preveem a diminuição do período de incubação para a ferrugem do cafeeiro (Ghini et al, 2011) e, portanto, epidemias mais severas, tendência que pode ser neutralizada pelo efeito de redução da doença, em razão do aumento da concentração de CO 2 , observado no presente trabalho. Considerandose a favorabilidade térmica e hídrica para a ocorrência da ferrugem do cafeeiro, há também a previsão de um decréscimo de épocas favoráveis à doença, em consequência do aumento da temperatura e diminuição da umidade relativa do ar (Pozza & Alves, 2008). )…”
Section: Resultsunclassified